MELANOMAS, SARCOMAS, AND RENAL METASTASES IN THE LIVER: HOW TO TREAT? - Angelica Maria LUCCHESE; Antonio Nocchi KALIL; Alessandro L. DINIZ; Karl J. OLDHAFER; Timothy M. PAWLIK; René ADAM; Olivier SOUBRANE; Maria Ignez BRAGHIROLI; Ricardo Lemos COTTA-PEREIRA (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT Liver metastases from melanomas, sarcomas, and renal tumors are less frequent. Treatment and prognosis will depend on whether they are isolated or multiple, size and location, the presence or absence of extrahepatic neoplastic disease, age, stage of the initial disease, initial treatments instituted, time of evolution, and clinical condition of the patient. Recently, a high number of oncological therapies including monotherapy or in combination, neoadjuvants or adjuvants, and immuno-oncological treatments have been developed and tested, increasing disease-free time and survival.